ANALISIS ETIKA KERJA ISLAM PADA KINERJA KARYAWAN BPRS MAU BANDAR LAMPUNG - Ansyori Ahmad (FKIP Unswagati, 2021)
AbstractIn this era, the world has developed. Thus, it requires a company to be able to compete and survive in the business. As a consequence, a company must be more effective and efficient in conducting its operational activities in order to ensure the survival of the company. The success of the company's operational activities can’t only be seen from the quality products it produces, but also from the services provided and the work ethic of the Human Resources in the company. And then, this research aimed to analyze how the application of Islamic work ethics to employees of BPRS Mitra Agro Usaha Bandar Lampung and how the application of Islamic work ethics affects the performance of employees of BPRS Mitra Agro Usaha Bandar Lampung. This research used field research with a qualitative approach and descriptive. Data collection used interviews and observations. The results of the research showed that employees of BPRS Mitra Agro Usaha Bandar Lampung had reflected the true work ethic of Muslims by applying the characteristics of Islamic work ethics such as honesty, discipline, creativity, being responsible, happy. Because they served and being independent in order to make BPRS Mitra Agro Usaha a transitioning Financing Bank from conventional to Sharia Financing Bank. The Bank completely applies Sharia working principles as per Islamic teachings. Furthermore, the application of Islamic work ethics had a positive impact on the performance of employees of PT. BPRS Mitra Agro Usaha Bandar Lampung.Keywords: Islamic Work Ethic, Employee Performance.